2014
DOI: 10.1136/gutjnl-2014-307075
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 regulates ERBB signalling in pancreatic cancer development

Abstract: By integrating data from patient samples and mouse models, we found that SOX9 regulates the ERBB pathway throughout pancreatic tumourigenesis. Our work opens perspectives for therapy targeting tumourigenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 42 publications
6
69
0
2
Order By: Relevance
“…Under inflammatory conditions, or in the presence of oncogenic KRAS, SOX9 is increasingly expressed in acinar cells and stimulates gene expression that leads to ADM 48 , development of pre-malignant lesions and initiation of PDAC in mice 14 . In line with these findings, SOX9 expression in patient tumour samples is elevated at all stages of preneoplastic lesions and PDAC 49 , correlating with increased expression of EGFR pathway-related genes 50 . Similarly, in mice, the absence of SOX9 reduces EGFR signalling and pancreatic tumorigenesis 50 .…”
Section: Acinar Cell Dedifferentiation Factorssupporting
confidence: 66%
See 1 more Smart Citation
“…Under inflammatory conditions, or in the presence of oncogenic KRAS, SOX9 is increasingly expressed in acinar cells and stimulates gene expression that leads to ADM 48 , development of pre-malignant lesions and initiation of PDAC in mice 14 . In line with these findings, SOX9 expression in patient tumour samples is elevated at all stages of preneoplastic lesions and PDAC 49 , correlating with increased expression of EGFR pathway-related genes 50 . Similarly, in mice, the absence of SOX9 reduces EGFR signalling and pancreatic tumorigenesis 50 .…”
Section: Acinar Cell Dedifferentiation Factorssupporting
confidence: 66%
“…In line with these findings, SOX9 expression in patient tumour samples is elevated at all stages of preneoplastic lesions and PDAC 49 , correlating with increased expression of EGFR pathway-related genes 50 . Similarly, in mice, the absence of SOX9 reduces EGFR signalling and pancreatic tumorigenesis 50 . However, EGFR signalling can also regulate expression of SOX9 through activation of NFATC1 and NFATC4 (REFS 51,52).…”
Section: Acinar Cell Dedifferentiation Factorssupporting
confidence: 66%
“…According to recent literatures, ErbB signaling pathway and TGF-beta signaling pathway participate in the transmembrane signal transduction of pancreatic cancer [13, 14]. Such transmembrane signal transduction pathways have been further validated to transfer the signals to intracellular pathways (such as p53 signaling pathway, MAPK signaling pathway, PI3K-Akt signaling pathway, and VEGF signaling pathway) [13, 1517]. Intracellular signaling pathways have been identified to contribute to the abnormal proliferation of pancreatic cells and further initiate the tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of pancreatic cancer, Sun et al found that the nuclear factor-κB signaling pathway can epigenetically regulate the expression of SOX9 and promote the invasiveness of CSCs (7). Grimont et al also demonstrated that SOX9 upregulated the ERBB signaling pathway to promote the tumorigenesis of pancreatic cancer (8). In addition, SOX9 is necessary for tumor cell initiation and division, self-renewal, and tumorigenicity in CSCs of hepatocellular carcinoma (9).…”
mentioning
confidence: 99%
“…Therefore, targeting of CSCs may be useful in cancer therapeutics. The crucial role played by SOX9 in CSCs has been verified in digestive system cancers, including pancreatic cancer and hepatocellular carcinoma (7)(8)(9). In a study of pancreatic cancer, Sun et al found that the nuclear factor-κB signaling pathway can epigenetically regulate the expression of SOX9 and promote the invasiveness of CSCs (7).…”
mentioning
confidence: 99%